função exponecial
Soluções para a tarefa
Respondido por
1
Oi Alison.
Dada a equação:
![9^{ x-1 }-5*3^{ x }+3^{ x+1 }=27 9^{ x-1 }-5*3^{ x }+3^{ x+1 }=27](https://tex.z-dn.net/?f=9%5E%7B+x-1+%7D-5%2A3%5E%7B+x+%7D%2B3%5E%7B+x%2B1+%7D%3D27)
![3^{ 2x-2 }-5*3^{ x }+3^{ x }*3=27\\ \\ 3^{ x }=y\\ \\ \frac { 3^{ 2x } }{ 3^{ 2 } } -5*3^{ x }+3^{ x }*3=27\\ \\ \frac { y^{ 2 } }{ 9 } -5y+3y=27\\ \\ \frac { y^{ 2 }-45y+27y=243 }{ 9 } \\ \\ y^{ 2 }-18y-243=0\\ \\ (y-27)(y+9)\\ \\ y-27=0\\ y=27\\ \\ y+9=0\\ y=-9 3^{ 2x-2 }-5*3^{ x }+3^{ x }*3=27\\ \\ 3^{ x }=y\\ \\ \frac { 3^{ 2x } }{ 3^{ 2 } } -5*3^{ x }+3^{ x }*3=27\\ \\ \frac { y^{ 2 } }{ 9 } -5y+3y=27\\ \\ \frac { y^{ 2 }-45y+27y=243 }{ 9 } \\ \\ y^{ 2 }-18y-243=0\\ \\ (y-27)(y+9)\\ \\ y-27=0\\ y=27\\ \\ y+9=0\\ y=-9](https://tex.z-dn.net/?f=3%5E%7B+2x-2+%7D-5%2A3%5E%7B+x+%7D%2B3%5E%7B+x+%7D%2A3%3D27%5C%5C+%5C%5C+3%5E%7B+x+%7D%3Dy%5C%5C+%5C%5C+%5Cfrac+%7B+3%5E%7B+2x+%7D+%7D%7B+3%5E%7B+2+%7D+%7D+-5%2A3%5E%7B+x+%7D%2B3%5E%7B+x+%7D%2A3%3D27%5C%5C+%5C%5C+%5Cfrac+%7B+y%5E%7B+2+%7D+%7D%7B+9+%7D+-5y%2B3y%3D27%5C%5C+%5C%5C+%5Cfrac+%7B+y%5E%7B+2+%7D-45y%2B27y%3D243+%7D%7B+9+%7D+%5C%5C+%5C%5C+y%5E%7B+2+%7D-18y-243%3D0%5C%5C+%5C%5C+%28y-27%29%28y%2B9%29%5C%5C+%5C%5C+y-27%3D0%5C%5C+y%3D27%5C%5C+%5C%5C+y%2B9%3D0%5C%5C+y%3D-9)
O -9 não serve.
![3^{ x }=27\\ 3^{ x }=3^{ 3 }\\ x=3 3^{ x }=27\\ 3^{ x }=3^{ 3 }\\ x=3](https://tex.z-dn.net/?f=3%5E%7B+x+%7D%3D27%5C%5C+3%5E%7B+x+%7D%3D3%5E%7B+3+%7D%5C%5C+x%3D3)
Dada a equação:
O -9 não serve.
Perguntas interessantes
Inglês,
1 ano atrás
Artes,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás